2021
DOI: 10.5194/isprs-archives-xlvi-4-w4-2021-25-2021
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Reality Capture for Subsurface Utilities: Experiences From Water Utility Companies in Denmark

Abstract: Abstract. Inaccurate and inconsistent documentation of subsurface utilities is a reoccurring problem in the construction industry affecting not only the end-users, but all actors involved in designing, constructing, and maintaining pipes, cables and other utilities hidden underground. In this study, a new method for 3D capturing of subsurface utilities, based on a newly developed Smartphone-based Reality Capture (RC) solution is explored. The research was divided into two parts. Firstly a testing of the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…These findings are in alignment with existing literature in observing that digital cameras outperform mobile phone cameras due to their better camera quality (Akca & Gruen, 2009). The results of the smartphones' horizontal errors were largely similar to the results in Hansen et al (2021) where a RMSEXY of 30.4mm was achieved. However, the vertical errors differed by around 20mm (the authors reported a RMSEZ of 32.6mm).…”
Section: Locational Accuracysupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in alignment with existing literature in observing that digital cameras outperform mobile phone cameras due to their better camera quality (Akca & Gruen, 2009). The results of the smartphones' horizontal errors were largely similar to the results in Hansen et al (2021) where a RMSEXY of 30.4mm was achieved. However, the vertical errors differed by around 20mm (the authors reported a RMSEZ of 32.6mm).…”
Section: Locational Accuracysupporting
confidence: 89%
“…Many of the existing photogrammetric applications are applied to the 3D reconstruction of objects situated above a surface, leaving a gap in understanding the photogrammetric potential for mapping excavated trenches. A commendable study by Hansen et al (2021) assessed the locational accuracy of water utilities by comparing two approaches: SfM technique with total station and GNSS-RTK. Smartphone-based video recordings of excavated pits were recorded, and it was concluded that the photogrammetric technique was a useful surveying method for capturing as-built utilities.…”
Section: Photogrammetry For Subsurface Utility Mappingmentioning
confidence: 99%
“…In the case of geological issues, the analysis of rock porosity and roughness is a common topic [ 65 , 66 ], while in geomorphology it is popular to create digital models of various types of geomorphological forms (e.g., cliffs, caves) [ 70 , 71 ]. In terms of industrial applications, it is worth noting displacement determination [ 78 , 79 ] and utility networks modeling [ 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hansen et al [19] suggest using construction and maintenance projects to improve documentation quality, and propose on-site documentation using photogrammetry or laser scanning, as well as utilizing…”
Section: Sue Data and Applicationsmentioning
confidence: 99%